Experimental Study on the Self-Healing Behavior of Fractured Rocks Induced by Water-CO2-Rock Interactions in the Shendong Coalfield - Jinfeng Ju; Quansheng Li; Jialin Xu (Geofluids)
This study experimentally investigated the self-healing behavior, referring to the naturally occurring water permeability decrease, of fractured rocks exposed to water-CO2-rock interaction (WCRI). The experiment was conducted on prefractured specimens of three rock types typical of the Shendong coalfield: coarse-grained sandrock, fine-grained sandrock, and sandy mudrock. During the experiment, which ran for nearly 15 months, all three specimens exhibited decreasing permeabilities. The coarse- and fine-grained sandrock specimens exhibited smooth decreases in permeability, with approximately parallel permeability time curves, whereas that of the sandy mudrock specimen decreased rapidly during the initial stage and slowly during later stages. The sandrock specimens were rich in feldspars, which were dissolved and/or corroded and involved in ionic exchange reactions with CO2 and groundwater, thereby generating secondary minerals (such as kaolinite, quartz, and sericite) or CaSO4 sediments. These derivative matters adhered to the fracture surface, thereby gradually repairing fractures and decreasing the water permeability of the fractured rocks. In comparison, the sandy mudrock had a high content of clay minerals, and the water-rock interaction caused rapid expansions of illite, mixed illite-smectite, and other clay minerals, thereby narrowing the fractures and causing the rapid permeability decrease during the initial stage. In later stages, the derivative matters generated by the dissolution and/or corrosion of feldspars and other aluminum silicate minerals in the mudrock filled and sealed the fractures, causing the slow permeability decreases during the later stages, as in the sandrock specimens. Neutral and basic groundwater conditions facilitated better self-healing of fractured mudrocks rich in clay minerals, whereas acidic groundwater conditions and the presence of CO2 facilitated better self-healing of fractured sandrocks. Thus, this study’s results are of significant value to aquifer restoration efforts in the Shendong coalfield and other ecologically vulnerable mining areas.